PENGARUH TINGKAT PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP INFORMATION ASYMMETRY DENGAN VARIABEL KONTROL DIVIDEND YIELD DAN MARKET-TO-BOOK RATIO PADA PERUSAHAAN TERBUKA DI INDONESIA - Anastasia Audina Candra; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimed to identify and to prove the existence of a relationship between Corporate Social Responsibility (CSR) disclosure level and the decreased levels of information asymmetry measured by using level of disclosure of CSR (TCSR). CSR disclosure level was measured by using the Sustainability Report that valued by the criteria of the GRI guideliness. The asymmetry of information that occured between company’s managers and investors measured by using the bid-ask spread. This study used control variables of the dividend yield and market-to-book ratio. This research was carried out on public companies inIndonesiawhich published sustainability report and listed in the GRI database with a sample of 111 observations. The results showed that there was a positive and significant affect of CSR disclosure level on information asymmetry. The results also showed that the dividend yield affected the bid-ask spread positively, while the market-to-book ratio had not affected the bid-ask spread.